Correlation Between Grain Size Distribution and Silicon and Oxygen Contents at Wadi Arar Sediments, Kingdom of Saudi Arabia - Alghamdi, M. A. M. (Engineering, Technology & Applied Science Research, 2017)
Quartz is the major mineral of Wadi Arar sediments. The top two elements contents are oxygen with 63.96 wt%, followed by silicon with 16.35 wt%. There is a positive, weak to medium correlation between grain size and silicon and oxygen contents. The correlation between oxygen and grain size is four times higher than that of silicon. At grain size ranges between 0.8 and 1.0 mm, both oxygen and silicon show the maximum correlation, which decrease gradually with finer and coarser grain sizes. For each element, the correlation between the element content and grain size is a fourth degree polynomial in the grain size. Theoretically, the best two math models that represent the relation between the grain size distribution and each of individual oxygen and silicon content are y=8.84∙ln(x)+39.5 and y=2.26∙ln(x)+10.1 respectively, where y represents the element content percentage and x represents the corresponding grain size in mm.